The role of research institutes in scientific support of state strategic plans - Arkenova, Zh.R.; Abramov, R.A. (BUKETOV BUSINESS REVIEW, 2020)
Object: Article determines the main directions and conceptual approaches of research institutions in the framework of scientific support for the methodology of strategic planning in modern conditions. Methods: The scientific abstraction method supported with information analysis and grouping. Results: This article discusses current problems and key tasks of modernizing scientific-methodological and information-analytical support for the state strategic management of socio-economic development. Main trends in the evolution of objects and subjects of management in the conditions of digital transformation of the information society are investigated. In addition, this research describes the institutional basis for building and functioning of the strategic planning system of the Republic of Kazakhstan. Also, the article presents a structural diagram of a complex of heterogeneous models of strategic planning of socio-economic development. Project solutions have been proposed to build architecture and develop a prototype computer support system for scenario modeling technology in the development of multi-level strategic solutions for the planning of socio-economic development in the emerging infrastructure of the digital economy. Conclusions: The study showed the importance and urgency of modernizing the methodological and analytical support of the strategic planning system of the Republic of Kazakhstan, considering the main consequences and requirements for the creation and dissemination of digital technologies in various spheres of society. The most important characteristics of innovative changes in the structure and content of strategic planning tasks, the solution of which relates to the unification of the format of presentation of quantitative and qualitative assessments in the digital environment have been revealed. This can improve the degree of validity and coherence of the planned decisions and regulatory measures developed by the state in the area of planning of socio-economic development and ensuring the national security of the Republic of Kazakhstan